2021
DOI: 10.2147/opth.s276335
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corneal Epithelial Thickness and Dry Eye Disease Tests in Thalassemic Adolescents

Abstract: Purpose To assess dry eye disease (DED) in thalassemic adolescents by evaluating corneal epithelial thickness (CET) and various dry eye clinical tests and correlate them to tissue iron overload. Methods The study included 120 Beta-thalassemia patients (11 to 18 years) and 120 matched controls. CET maps were captured using anterior segment optical coherence tomography. OSDI questionnaire was completed. Dry eye tests included Schirmer test, tear film breakup time ‎‎ (TBUT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…In a study, the authors found significantly thicker central, paracentral, and midperipheral CET and a similar increase in stromal thickness in patients with diabetes compared to normal group [ 205 ]. Another study demonstrated reduced corneal thickness in adolescents with thalassemia major; high serum transferrin levels and liver iron concentrations were associated with reduced corneal thickness [ 206 ]. Another study found decreased epithelial thickness in patients with Graves' disease regardless of orbitopathy presence.…”
Section: Systemic Conditionsmentioning
confidence: 99%
“…In a study, the authors found significantly thicker central, paracentral, and midperipheral CET and a similar increase in stromal thickness in patients with diabetes compared to normal group [ 205 ]. Another study demonstrated reduced corneal thickness in adolescents with thalassemia major; high serum transferrin levels and liver iron concentrations were associated with reduced corneal thickness [ 206 ]. Another study found decreased epithelial thickness in patients with Graves' disease regardless of orbitopathy presence.…”
Section: Systemic Conditionsmentioning
confidence: 99%